A Bibliometrik Analysis of Crowdfunding in Smes : A Decade Study Based on Sopus Scientific Mapping - Edi Murdiyanto; Sudarmiatin; Ludi Wishnu Wardana (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study aims to describe and illustrate quantitative bibliometrics. Validity and relational techniques were used to generate outcome findings and map research themes, impacts, directions, and collaboration trends. Topic classification is also included to review results from different types of analysis. The theme of the Scopus publication is SMEs Crowdfunding. This began to be heavily researched in 2019 and peaked in 2020. From the analysis, it is stated that SMEs Crowdfunding is widely discussed in relation to various research themes. One of the interesting ones is related to women entrepreneurship.  SMEs have difficulty accessing funding, so the emergence of Crowdfunding is an alternative financing. Bibliometric analysis is used to examine bibliographic data collected from the Scopus database. SMEs have difficulty accessing funding, so the emergence of Crowdfunding is one of the financing alternatives. Bibliometric analysis is used to test bibliographic data collected from the Scopus database.